2022
DOI: 10.1002/adfm.202207749
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin‐Based Covalent Organic Framework for Imaging‐Guided Cancer Combinatorial Immuno‐Sonodynamic Therapy

Abstract: The rational design of tumor microenvironment (TME)‐activated nanomedicine is driving a new direction in tumor immunology. Furthermore, the novel therapeutic mode of ultrasound‐triggered sonodynamic therapy (SDT) has been proven to specifically activate the immune response. Herein, a well‐defined covalent organic framework (COF) with sonosensitive properties is synthesized through experimental and theoretical verification, followed by the efficient loading of the toll‐like receptor agonist (Poly(I:C)) and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Covalent organic frameworks (COFs), which are crystalline porous polymeric materials with well-dened chemical structures, [25][26][27][28][29][30] have attracted extensive research interest in the tumor nanomedicine eld, and have been used in drug delivery, [31][32][33][34][35][36] phototherapy, [37][38][39][40][41][42][43][44][45][46] and immunotherapy [47][48][49][50][51][52] because they are versatile and biocompatible. Recently, AgI@COF-TpBpy was used as a delivery vehicle for radioiodine in brachytherapy, showing a long tumor retention time and effective cancer cell killing performance; 53 however, to our knowledge, the potential of a metal-free COF itself as a radiosensitizer in radiotherapy has not been exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs), which are crystalline porous polymeric materials with well-dened chemical structures, [25][26][27][28][29][30] have attracted extensive research interest in the tumor nanomedicine eld, and have been used in drug delivery, [31][32][33][34][35][36] phototherapy, [37][38][39][40][41][42][43][44][45][46] and immunotherapy [47][48][49][50][51][52] because they are versatile and biocompatible. Recently, AgI@COF-TpBpy was used as a delivery vehicle for radioiodine in brachytherapy, showing a long tumor retention time and effective cancer cell killing performance; 53 however, to our knowledge, the potential of a metal-free COF itself as a radiosensitizer in radiotherapy has not been exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is a major contributor to radio-resistance. Thus, tumor re-oxygenation strategies, including the use of oxygen-saturated nanomaterials (perfluorocarbon), 115 oxygen-generators (MnO 2 ), 116 NO-releasing prodrugs, 117 HIF-1α inhibitor-containing carriers, 118 catalase, catalase-like metals or H 2 O 2 , 119 have been employed to address tumor hypoxia-induced radioresistance. iii.…”
Section: Nanomedicines Aid In Cancer Radio-immunotherapymentioning
confidence: 99%
“…MnO 2 nanomedicine-mediated immunomodulation and radiosensitization have been discovered to some extent: Mn 2+ augments the STING signaling and hypoxia-mediated radioresistance is relieved by oxygen generation in a MnO 2 -mimic catalyst decomposition of over-expressing H 2 O 2 in TME. 116…”
Section: Considerations For Clinical Translation and Future Directionsmentioning
confidence: 99%
“…Researchers have shown that the Fenton reaction can cause oxidative damage to the cancer cells' DNA, proteins, or lipids, which can be targeted for treatment [118]. Te right conditions are created for the Fenton reaction (Fe 2+ + H 2 O 2 ⟶ Fe3 + + •OH + OH−) to take place by the overexpression of H 2 O 2 (100 M) and moderate acidity of TME [119].…”
Section: Fenton-reaction Approachmentioning
confidence: 99%